Differentiation of Population by Income and Possible Ways of It’s Solution ("Journal "U". Economy. Management. Finance.", 2021)
In conditions of macroeconomic instability, negative phenomena are increasing. One of these is the income inequality of the population. The main problems were identified by analyzing statistical indicators. Possible ways of solving them are presented in the article.
Keywords: income; wage; income differentiation; decile coefficient; Gini coefficient